Role of a Novel I1781T Mutation and Other Mechanisms in Conferring Resistance to Acetyl-CoA Carboxylase Inhibiting Herbicides in a Black-Grass Population - Kaundun, Shiv Shankhar; Hutchings, Sarah-Jane; Dale, Richard P.; McIndoe, Eddie (PLOS ONE, 2013)
Background Knowledge of the mechanisms of herbicide resistance is important for designing long term sustainable weed management strategies. Here, we have used an integrated biology and molecular approach to investigate the mechanisms of resistance to acetyl-CoA carboxylase inhibiting herbicides in a UK black-grass population (BG2). Methodology/Principal Findings Comparison between BG2 phenotypes using single discriminant rates of herbicides and genotypes based on ACCase gene sequencing showed that the I1781L, a novel I1781T, but not the W2027C mutations, were associated with resistance to cycloxydim. All plants were killed with clethodim and a few individuals containing the I1781L mutation were partially resistant to tepraloxydim. Whole plant dose response assays demonstrated that a single copy of the mutant T1781 allele conferred fourfold resistance levels to cycloxydim and clodinafop-propargyl. In contrast, the impact of the I1781T mutation was low (Rf = 1.6) and non-significant on pinoxaden. BG2 was also characterised by high levels of resistance, very likely non-target site based, to the two cereal selective herbicides clodinafop-propargyl and pinoxaden and not to the poorly metabolisable cyclohexanedione herbicides. Analysis of 480 plants from 40 cycloxydim resistant black grass populations from the UK using two very effective and high throughput dCAPS assays established for detecting any amino acid changes at the 1781 ACCase codon and for positively identifying the threonine residue, showed that the occurrence of the T1781 is extremely rare compared to the L1781 allele. Conclusion/Significance This study revealed a novel mutation at ACCase codon position 1781 and adequately assessed target site and non-target site mechanisms in conferring resistance to several ACCase herbicides in a black-grass population. It highlights that over time the level of suspected non-target site resistance to some cereal selective ACCase herbicides have in some instances surpassed that of target site resistance, including the one endowed by the most commonly encountered I1781L mutation.